واجهة رسومية لنظام البريد الالكتروني - مساعيد محمد الاخضر مسلم شعيب عوادي محمد علي (university of eloued جامعة الوادي, 2024)
يعتبر البريد الإلكتروني محوراً أساسياً لتطوير نظام تواصل رقمي حديث يعتمد على خدمات المراسلة، والتي تعد جزءا لا يتجزأ من حياتنا اليومية والأعمال ، وتكمن أهمية الموضوع في تصميم واجهة رسومية مبتكرة لنظام البريد الإلكتروني تساهم في تحسين تجربة المستخدم من خلال تقديم واجهة سهلة الاستخدام وجذابة. هذا يعزز من كفاءة إدارة البريد الإلكتروني وزيادة الإنتاجية، ويضمن حماية البيانات وتحقيق رضا المستخدمين، مما يجعل النظام أكثر فعالية ومرغوباً فيه .تواجه أنظمة البريد الإلكتروني الحالية تحديات في توفير تجربة مستخدم فعالة ومريحة، حيث تفتقر بعض الواجهات الرسومية إلى السهولة في الاستخدام والتصميم الجذاب، مما يؤدي إلى صعوبة في إدارة البريد الإلكتروني وانخفاض الإنتاجية. هذه الاخيرة جعلتنا نشرع في تصميم واجهة رسومية سهلة الاستخدام تحتوى على نظام ارسال سلس ومتكامل بين المستخدمين Email is considered an essential axis for developing a modern digital communication system based on Messaging services, which are an integral part of our daily life and business, and the importance of the topic lies in designing an innovative graphical interface for the e-mail system that contributes to improving the user experience by providing an easy-to-use and attractive interface. This enhances email management efficiency, increases productivity, ensures data protection and user satisfaction, making the system more effective and desirable. Current email systems face challenges in providing an efficient and convenient user experience, as some graphical interfaces lack ease of use and attractive design, leading to difficulty in email management and decreased productivity. The latter made us begin to design an easy-to-use graphical interface that contains a smooth and integrated transmission system between users
مدكرة ليسانس اعلام الي
Keywords: بريد الإلكتروني; واجهة رسومية. انجليزية: - Email; Graphical User Interface (GUI)